2019
DOI: 10.1080/23802359.2019.1617074
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Elaeagnus conferta Roxb (Elaeagnaceae)

Abstract: Elaeagnus conferta Roxb is a kind of fruit known for its oval shape, bright red colour, and sour and sweet taste. In this study, we assembled and characterized the complete chloroplast genome of E. conferta Roxb as a resource for future genetic studies. With a total length of 151,751 bp, the chloroplast genome has a total of 130 genes, consisting of 88 protein-coding genes, 34 tRNA genes, and 8 rRNA genes. Phylogenetic analysis confirmed the position of E. conferta Roxb within the order Rosales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Previous phylogenetic studies using several gene regions revealed three well-supported clades in the genus Elaeagnus L. ( Liu et al, 2019 ; Alexandrov and Karlov, 2021 ). Similarly, our results indicated that both MP and ML trees showed three or four well-supported clades in the genus Elaeagnus L. For the first time, we used the matK sequence of the DNA marker region of the chloroplast genome, and the obtained molecular phylogeny was concordant with the morphological taxonomy.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous phylogenetic studies using several gene regions revealed three well-supported clades in the genus Elaeagnus L. ( Liu et al, 2019 ; Alexandrov and Karlov, 2021 ). Similarly, our results indicated that both MP and ML trees showed three or four well-supported clades in the genus Elaeagnus L. For the first time, we used the matK sequence of the DNA marker region of the chloroplast genome, and the obtained molecular phylogeny was concordant with the morphological taxonomy.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, it is interesting that the selection and breeding based on the excellent genetic material of E. conferta have been developed for nearly 20 years in mainland China ( Gill and Gupta, 2018 ; Liu et al, 2019 ). E. conferta has an absolute advantage in fruit size, but distribution is limited in China’s low latitude subtropical regions, such as Yunnan and Guangxi Provinces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete genome of E. angustifolia, as well as the E. macrophylla and E. conferta Roxb. chloroplast genomes, has been recently sequenced [5][6][7]. Furthermore, several attempts have been made to identify species in the Elaeagnus by using DNA barcoding when determining phylogenetic relationships and describing new species [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover it is reported that silver nano particles of leaf extract of E. conferta has been prepared and has wide application in field of pharmacology and industries (Gowtham Prasanth E, 2017;Phanjom et al, 2012). In traditional herbal medicine, the fruit, leaves and roots have been explored for the ailment of multiple diseases such as diabetes, ulcer, pain, rheumatism, diarrhea, inflammation and pulmonary disorders (Binu, 2011;Deshmukh and Waghmode, 2011;Gill and Gupta, 2018;Jin et al, 1999;Liu et al, 2019;Patil et al, 2012;Raghavendra et al, 2015;Rana and Samant, 2011). Fruits, either raw or in the form of juice, syrup, pickle, jelly etc, have been reported to be used as food supplement and is free from any side effects (Deshmukh and Waghmode, 2011).…”
Section: Introductionmentioning
confidence: 99%